2011
DOI: 10.1371/journal.pone.0026888
|View full text |Cite
|
Sign up to set email alerts
|

Venom of Parasitoid, Pteromalus puparum, Suppresses Host, Pieris rapae, Immune Promotion by Decreasing Host C-Type Lectin Gene Expression

Abstract: BackgroundInsect hosts have evolved immunity against invasion by parasitoids, and in co-evolutionary response parasitoids have also developed strategies to overcome host immune systems. The mechanisms through which parasitoid venoms disrupt the promotion of host immunity are still unclear. We report here a new mechanism evolved by parasitoid Pteromalus puparum, whose venom inhibited the promotion of immunity in its host Pieris rapae (cabbage white butterfly).Methodology/Principal FindingsA full-length cDNA enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 65 publications
2
24
0
Order By: Relevance
“…Especially, it was reported that the gene lectin - 24A was massively up-regulated in parasitized Drosophila larvae after parasitization at the time when the capsule was formed [51]. A similar investigation indicated that the inhibitory effect of P. puparum venom on host encapsulation is consistent with its effect in suppressing CTL expression [52]. Thus, CLT is an important immune candidate involved in the suppression of host cellular immune defense induced by the parasitoid.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Especially, it was reported that the gene lectin - 24A was massively up-regulated in parasitized Drosophila larvae after parasitization at the time when the capsule was formed [51]. A similar investigation indicated that the inhibitory effect of P. puparum venom on host encapsulation is consistent with its effect in suppressing CTL expression [52]. Thus, CLT is an important immune candidate involved in the suppression of host cellular immune defense induced by the parasitoid.…”
Section: Resultsmentioning
confidence: 79%
“…For example, transcript levels of cecropin and gloverin in eggs of M. sexta were suppressed after parasitization by Trichogramma evanescens [57]. After Pieris rapae pupae injected with P. puparum venom, ten potential antimicrobial molecules including cecropin, lysozyme, attacin, lebocin, proline-rich AMP, cysteine-rich peptide, gallerimycin and immune inducible peptide had lower transcript levels in hemocytes or fat body of the venom injected hosts[52], demonstrating that the transcriptional down regulation of these antimicrobial genes is due to the venom. Nevertheless, parasitization of Drosophila resistant strain by the corresponding parasitoids did not induce transcripts of diptericin and cecropin whilst the susceptible strain did [55], [56].…”
Section: Resultsmentioning
confidence: 99%
“…This gene (GAJS01016295) was down-regulated (log 2 Ratio  =  –4.9) in fatbody and up-regulated (log 2 Ratio  =  12.9) in hemocytes (Table 3). Although PRRs are up-regulated by infections [38], these genes can be suppressed by parasitoid venom [20], [21] or PDVs [39]. In our results, certain PRRs included peptidoglycan recognition protein B (GAJS01023399, PF/CF: –1.2), hemicentin 1 (GAJS01000005, PH/CH: –4.5), leureptin (GAJS01018114, PF/CF: –4.5) and Scavenger receptor class B (GAJS01011562, PH/CH: –2.2) were down-regulated.…”
Section: Resultsmentioning
confidence: 99%
“…Other virulence factors found in some parasitoids, such as PDVs, virus-like particles, or teratocytes, have not been recorded in P. puparum (29). As the major maternal virulence factor in P. puparum, P. puparum venom regulates host development and metabolism (30) and suppresses cellular (27,28,31) and humoral immunity of the host (32)(33)(34). Here we report a serpin gene with 16 predicted splicing isoforms in P. puparum and show that one of these isoforms is a venom protein, which inhibits host PPO activation by forming complexes with host hemolymph proteinases.…”
mentioning
confidence: 99%